Assessing the Product Quality of Meat Processing Companies and Costs on Quality Improvement - Gennadievich Shtefan, Yan; Aleksandrovna Zimakova, Liliya; Nikolaevich Aleynik, Stanislav; Borisovich Tresnitskiy, Aleksey; Leonidovna Kidanova, Natalia (International Journal of Engineering and Technology, 2018)
Within the context of new economic conditions, the issues of quality become a priority that allows gaining competitive advantages, on the one hand, and satisfy the ever-growing needs of consumers, on the other hand. Meat processors carry out the multilevel quality control both of their products and of the processes: the quality issues are of particular importance for such companies; that is why they were chosen as the object of research. The article deals with the issues of evaluating the product quality and analyzing the effectiveness of quality costs. The authors propose to use the integral factor of product quality in practice as it includes the mathematical assessment of technical and consumer criteria and the product safety criterion. The recommendations allow reducing the complexity of the assessment process, improving the quality of information, and simplifying the procedure of control and analysis with regard to obtaining long-term competitive advantages that lead to an increase in a company’s value.